Staphylococcal toxic shock syndrome associated with disseminated intravascular coagulopathy leading to compartment syndrome of the lower extremity - Martin F. Vierhapper; Denise Traxler; Christine Radtke (Elsevier, 2017)
We report a case of a 56-year old multimorbid male patient who was transferred to our specialized burn center with a combination of extensive blistering with underlying deep tissue necrosis, disseminated intravascular coagulation and compartment syndrome to the left lower extremity. He was treated with high doses of intravenous antibiotics, above the knee amputation and multiple necrosectomy but died after 51 days due to multi organ failure.We believe that a rare combination of infection causing severe toxic shock syndrome leading to disseminated intravascular coagulation that then caused atraumatic compartment syndrome was responsible for this condition. Keywords: Staphylococcal toxic shock syndrome, Disseminated intravascular coagulopathy, Compartment syndrome